2015
DOI: 10.1371/journal.pone.0133128
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Attributable to Asbestos Exposure in Shipbreaking Workers: A Matched-Cohort Study

Abstract: PurposeLong-term follow-up studies of asbestos-related cancer in shipbreaking workers are lacking. This study examines the relationship between cancer incidence and asbestos exposure among former Taiwan shipbreaking workers.MethodsA total of 4,427 shipbreaking workers and 22,135 population-based matched controls were successfully followed in this study. The study cohort was linked to the Taiwan Cancer Registry for new cancer cases. The adjusted hazard ratio (aHR) for cancer was calculated for the shipbreaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
2
35
0
4
Order By: Relevance
“…Several cohort studies also suggested an increased risk of liver cancer in subjects exposed to asbestos. 110,111 for iCCA risk was reported among subjects occupationally exposed to asbestos for over 30 years; a limited evidence was instead reported for eCCA (OR = 2.09, 95% CI 0.83-5.27). 112 ).…”
Section: Environmental Exposurementioning
confidence: 99%
“…Several cohort studies also suggested an increased risk of liver cancer in subjects exposed to asbestos. 110,111 for iCCA risk was reported among subjects occupationally exposed to asbestos for over 30 years; a limited evidence was instead reported for eCCA (OR = 2.09, 95% CI 0.83-5.27). 112 ).…”
Section: Environmental Exposurementioning
confidence: 99%
“…The workers of the ship breaking industries have to work in a hostile environment with toxic substances like asbestos, thus they suffered from overall cancer, esophagus cancer, trachea bronchus and lung cancer etc (Wu et al, 2015 andMuhibbulahh et al, 2014). In case of the injuries and diseases suffered by the workers in the Sitakunda ship breaking yards, the loss of body parts is the most serious one.…”
Section: Risk Of Death Injury and Health Hazardsmentioning
confidence: 99%
“…A total of 14 studies that met the eligibility criteria were included in the review (Figure ). The majority of studies were conducted in European countries ( n = 6), including Sweden, France, Serbia, and the Netherlands .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were conducted in European countries ( n = 6), including Sweden, France, Serbia, and the Netherlands . Four studies were conducted in the United States, 2 in Taiwan, and 1 study each in Malaysia and Puerto Rico . Most studies included in the systematic review used the case‐control design, except 2 studies, one of which used a prospective longitudinal study design and the other a retrospective matched‐cohort study design .…”
Section: Resultsmentioning
confidence: 99%